ANALYSIS OF HUMAN GOVERNANCE IN THE INCLUSIVE VILLAGE PROGRAM FOR PEOPLE WITH DISABILITIES IN BEDALI VILLAGE LAWANG DISTRICT MALANG REGENCY - Muhammad Zaky Dharmawan; Sri Wibawani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
An inclusive village is a living space for a diverse community. Inclusive village governance is managed in an innovative and humanistic manner. This is in accordance with the theory of human governance. Human governance is a new culture for public administration. It can also be referred to as an effort to humanize public administration as a view that wants to explain different and innovative perspectives. This study aims to analyze human governance in an inclusive village program for persons with disabilities in Bedali Village, Lawang District, Malang Regency. The method used in this study is a qualitative descriptive approach using the theory of human governance. Data collection techniques were carried out through interviews, observation, and documentation. The results of this study indicate that the inclusive village program in Bedali Village has not fully met the principles of human governance because of the 9 principles of achieving goals. There are still 7 principles that can be implemented well from the inclusive village program which includes education for citizens, equality and freedom, participation, sustainability, subsidy assistance, adaptive government administration performance, and reliability. Social accountability has not been successful because of the absence of an inclusive village accountability report. Meanwhile, competition at the global level has not been successful because there are no village regulations regarding inclusive villages.